Impact of symptom presentation on in-hospital outcomes in patients with acute myocardial infarction. Issue 1 (July 2017) - Fujino, Masashi; Ishihara, Masaharu; Ogawa, Hisao; Nakao, Koichi; Yasuda, Satoshi; Noguchi, Teruo; Ozaki, Yukio; Kimura, Kazuo; Suwa, Satoru; Fujimoto, Kazuteru; Nakama, Yasuharu; Morita, Takashi; et al.
Abstract: Background: Limited data exist regarding the association between symptom presentation of acute myocardial infarction (AMI) and in-hospital outcomes. Methods: We analyzed data of the Japanese registry of acute Myocardial INfarction diagnosed by Universal dEfiniTion (J-MINUET). This was a prospective and multicenter registry consisting of 3085 AMI patients with available data of symptoms, who were hospitalized within 48 h from onset during July 2012 to March 2014. We defined typical symptoms as any of chest pain or pressure due to myocardial ischemia. Results: Of this study population, 642 patients (20.8%) had atypical symptoms (atypical group) and the remaining 2443 patients (79.2%) showed typical symptoms (typical group). Compared to the typical group, the atypical group was associated with higher age, more females, hypertension, diabetes, chronic kidney disease, history of cardiovascular disease, non-ST elevation MI, and Killip class ≥2. In the atypical group, urgent percutaneous coronary intervention was less frequently performed than in the typical group, and in STEMI patients door-to-balloon time was longer in the atypical than typical group. Atypical group had larger infarct size than typical group. Furthermore, in-hospital mortality was significantly higher in atypical than in typical group (19.5% vs. 3.3%, p  < 0.001). In multivariable analysis, presence of atypical symptoms was an independent predictor of in-hospital mortality (odds ratio 3.12, 95% confidence interval 2.19 to 4.47, p  < 0.001). Moreover, the association between atypical symptoms and mortality was consistent across each subgroup. Conclusions: Atypical symptoms of AMI were associated with less invasive therapy and poor outcome. Attention should be directed to these high-risk patients.